Ultra-light Colorless and Green Glass Foam Produced by Microwave Radiation - Lucian Paunescu; Sorin Mircea Axinte; Felicia Cosmulescu; Marius Florin Dragoescu; Bogdan Valentin Paunescu (Journal La Multiapp, 2021)
Abstract According to the research objective that was the basis of the paper, an ultra-light glass foam with an apparent density of 0.14 g/cm3 was experimentally made from 98.9% post-consumer glass bottle and 1% CaCO3 as a foaming agent by sintering/foaming at 823 ºC in microwave field with a very low specific energy consumption (0.70 kWh/kg). A very advanced mechanical processing of glass waste (below 32 μm) and a very fine granulation (below 6.3 μm) of CaCO3 were the solutions adopted to obtain this high-performance product. The originality of the work is the use of the unconventional technique of predominantly direct microwave heating with a very high energy efficiency, applied by authors in recent years and presented in several previous papers.